EFFECTS OF SLAUGHTER’ AGE ON GROWTH PERFORMANCE, CARCASS AND NON-CARCASS COMPONENTS TRAITS OF BERBER BREED LAMBS - Atroun, S.; Aissaoui, C.; Smeti, S.; Atti, N. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The objective of this work was to study the lamb’s growth, the carcass yield and composition and the importance of main organs of Berber lambs slaughtered at 4 or 6 months. The study concerned 40 lambs reared under motherhood. Lambs of the first group were slaughtered at the age of 4 months (4M) and the second at 6 months (6M). Slaughter body weights (BW), hot and cold carcass weights and organs were recorded. The carcass was cut out and dissected. The average BW at birth was 4.14 + 0.506 kg while the BW at slaughter was 22.86 kg + 3.40 and 31.51 + 3.50 kg for 4M and 6M groups, respectively. The average daily gain were 172 and 164g for 4M and 6M groups, respectively. Therefore, during 2months the lambs of 6M group gained 8.67 kg in BW. The carcasses were heavier for 6M than 4M. The carcass commercial yields were 42% and 45% for 4M and 6M groups, respectively, resulting in 4.1 kg gain of meat during 2 months. The tissular (muscle, fat and bone) and the regional (leg, shoulder …) carcass composition did not differ among groups. All organs were heavier for 6M than 4M; however, their proportion in the empty body weight were variables. The BWand carcass gain at six months are encouraging to prolong the lamb’s slaughter age without carcass composition difference given the similar fat proportion in the carcass of both groups.